2021
DOI: 10.4103/joacp.joacp_339_19
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Baska mask as an alternative airway device to endotracheal tube in patients undergoing laparoscopic surgeries under controlled ventilation

Abstract: Background and Aims: Newer supraglottic devices with an additional gastric channel offer greater protection from aspiration and avoidance of laryngoscopy for their insertion would result in attenuated hemodynamic responses.The primary objective was to assess hemodynamic responses to insertion of Baska mask as compared to tracheal intubation. The time and attempts taken to secure airway and evidence of regurgitation and pulmonary aspiration of gastric contents were also assessed. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Also, Abdel-Ghaffar et al (7) aimed to assess how the blood flow changed when a Baska mask was put on versus when a tracheal tube was put in. The time and number of attempts to open the airway, as well as any signs of regurgitation or pulmonary aspiration of stomach contents, were also taken into considerations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Abdel-Ghaffar et al (7) aimed to assess how the blood flow changed when a Baska mask was put on versus when a tracheal tube was put in. The time and number of attempts to open the airway, as well as any signs of regurgitation or pulmonary aspiration of stomach contents, were also taken into considerations.…”
Section: Discussionmentioning
confidence: 99%
“…These traits may make it less likely that secretions or stomach contents will get into the lungs if they build up in the supraglottic area (6) . Due to these modifications, the BASKA mask airway is now a desirable, safe, and efficient airway equipment for low-risk patients undergoing gynecologic laparoscopic surgery (7) .…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of OLP, analyzed in previous studies, showed that the OLP of the Baska mask was higher than that of other SADs, such as laryngeal mask Supreme™ (Teleflex, Inc., Wayne, PA, USA), and slightly lower than that of ET ventilation [ 7 , 9 , 12 , 15 , 28 ]. According to a previous study, the reported OLP of the Baska mask ranged from 33.3 to 36.6 cmH 2 O [ 12 , 22 ]. In our study, the mean OLP of the Baska mask was maintained at over 30 cmH 2 O throughout the operation.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the unique feature of the Baska mask, in which a cylindrical tube with a high-pressure and flow-suction system is available to remove oropharyngeal and gastric secretions and fluids. Tosh et al [ 12 ] also reported no difference in the regurgitation and aspiration of gastric contents between the Baska mask and ET in laparoscopic cholecystectomy, which was evaluated by bronchoscopic detection of methylene blue in the trachea and bronchus at the end of the operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation